1994
DOI: 10.1007/bf02638059
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and characterization ofDimorphotheca pluvialis seed oil

Abstract: Dimorphotheca pluvialis is increasingly recognized as an interesting industrial new oilseed crop because it contains up to 60% of the unusual fatty acid dimorphecolic acid (9‐hydroxy,10t,12t‐18∶2) (DA) for which new applications are being developed. In this paper, the yield, composition and quality are evaluated for dimorphotheca oils (DMO) which were recovered by pressing, conventional solvent extraction and supercritical carbon dioxide extraction (SCE). Mechanical pressing of the seeds required high temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Furthermore, 13-E,E-HODE (1), which is a geometrical isomer of 13-HODE, was also isolated as a weak PPARg agonist. Hydroxy unsaturated fatty acids occur in various organism species, and 13-E,E-HODE (1), 20) 9-E,E-HODE (2), 21) and other hydroxy unsaturated fatty acids 22) have already been isolated from plants and fungi, although there are few studies on their biological activity. Both 9-HODE and 13-HODE are produced by cyclooxygenase and/or lipoxygenase in mammalian cells such as endothelial, epithelial, and smooth muscle cells, as well as blood cells including neutrophils, basophils, monocytes, and lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 13-E,E-HODE (1), which is a geometrical isomer of 13-HODE, was also isolated as a weak PPARg agonist. Hydroxy unsaturated fatty acids occur in various organism species, and 13-E,E-HODE (1), 20) 9-E,E-HODE (2), 21) and other hydroxy unsaturated fatty acids 22) have already been isolated from plants and fungi, although there are few studies on their biological activity. Both 9-HODE and 13-HODE are produced by cyclooxygenase and/or lipoxygenase in mammalian cells such as endothelial, epithelial, and smooth muscle cells, as well as blood cells including neutrophils, basophils, monocytes, and lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…40-60°C), and subsequently the obtained oil was transesterified and hydrogenated as previously described [5][6][7][8][9]. The description for the production of the compounds 1 and 2 is reported by Bogaert et al [10].…”
Section: Analysis Of the Compoundsmentioning
confidence: 99%
“…Research on a broad range of new oilseed crops has resuited in insight in the optimal recovery routes for their oils and fatty acids. Some of the products can be recovered with conventional techniques, while others may require the use of modified or new technology (2)(3)(4)(5).…”
Section: General Assumptions and Technical Informationmentioning
confidence: 99%
“…However, conventional processing (pressing, solvent extraction, and especially refining of dimorphotheca oil) can lead to extensive deterioration of the dimorphecolic acid, e.g., thermal and chemical dehydration and cross-linking (10). Pilot-scale supercritical CO 2 extraction experiments showed that oil with chemically intact dimorphecolic acid and low in pigments and gums can be produced (2)(3)(4)(5).…”
Section: General Assumptions and Technical Informationmentioning
confidence: 99%